Coexistence of neuroendocrinal rectal tumour and pulmonary tuberculosis – diagnostic difficulties - Kula, Zbigniew; Kowalewski, Janusz; Szefer, Jarosław (Contemporary Oncology/Współczesna Onkologia, 2008)
A case of a 48 year old patient who had a rectum polyp of a texture of neuroendocrinological carcinoma of a low grade of malignancy and tubular adenoma with a small degree dysplasia removed endoscopically. The radiogram of the thorax and computed thomography (CT) examinations displayed round shadow of the right lung. The somatostatine receptor scintigraphy (SRS) displayed focal radioisotope uptake in the right lung. In the fusion positron emission tomography and CT (PET/CT) examination two focuses of increased glucose metabolism were found in the right lung. The patient was treated operationally. Histopathological examination of the postoperational preparation exhibited nodulo-caseous pulmonary tuberculosis with fibrosis. The presented case describes a very rare coexistence of rectal carcinoid and tuberculosis of the lung. We would like to emphasize that in these cases SRS and PET/CT may exhibit false positive results which makes differential diagnostics, establishment of clinical advancement of carcinoma and the choice of appropriate treatment difficult.